Russian foreign trade after four months of war in Ukraine - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
This brief examines the development of Russia's trade flows in the March-June period following Russia's invasion of Ukraine. Russia ceased publication of foreign trade statistics after the war broke out, so we utilize the trade statistics of Russia's major trading partners. We find that Russia's imports declined substantially in the period with the country struggling to find alternative import sources. On the other hand, Russian export revenues increased post-invasion due to high commodity prices, the lag in transition periods for EU import restrictions and higher export volumes going to other markets. Russian industrial output reflects a shift in foreign trade. High-tech industries reliant on imported inputs contracted, while output remained robust for some export-oriented industries. The first months of war show sanctions took an increasing toll on the Russian economy, seriously eroding the country's long-term growth potential.
urn:nbn:fi:bof-202209091354
Keywords: 330; Russia; trade; sanctions